Synergistic in vitro activity between aztreonam and amoxicillin–clavulanate against Enterobacteriaceae-producing class B and/or class D carbapenemases with or without extended-spectrum β-lactamases. Issue 9 (30th July 2019) - Ract, Pauline; Compain, Fabrice; Robin, Frédéric; Decre, Dominique; Gallah, Salah; Podglajen, Isabelle
Abstract : Introduction. Carbapenemase-producing Enterobacteriaceae have become a major public health concern over the last decade and treatment options are limited. Aims. We evaluated the synergistic activity of the combination of aztreonam (ATM) and clavulanate for 41 β -lactam-resistant clinical isolates harbouring class B or/and class D carbapenemases combined or not with extended-spectrum β -lactamases (ESBLs). Methodology. The MICs of ATM, with and without amoxicillin–clavulanate (AMC), were determined. Time-kill assays were performed for three representative strains. Results. The ATM–AMC combination had a synergistic effect on 34/41 (83 %) isolates. The MIC of ATM, in the presence of clavulanate, was ≤1 mg l −1 for 15/41 (37 %) isolates and ≤4 mg l −1 for 29/41 (71 %) isolates. Synergistic activity was observed for 34/37 (92 %) isolates producing ESBLs and carbapenemases, compared to 0/4 (0 %) for ESBL-negative strains. Complete or partial bactericidal activity was obtained when the MIC of the combination was 0.5 mg l −1 and 1.5 mg l −1 or 8 mg l −1, respectively. Conclusion. The combination of ATM and AMC could be an attractive unconventional treatment for infections due to carbapenemase- and ESBL-producing Enterobacteriaceae.